Evaluation of the lubricating power of sweet almond oil without additives (2018)
The lubricity of sweet almond oil (Prunus amygdalus var. Dulcis) was evaluated through Anti Wear (AW) properties and Extreme Pressure (EP) performance in a four-ball tribometer. The results were compared to those obtained with two mineral oils of contrasting viscosity, namely technical white mineral oil and delta 360 plasticizer, neither of them containing additives. Sweet almond oil was found to have greater lubricity than the mineral oils, as the spheres it lubricated had lower average wear track diameter and friction coefficient. In addition, sweet almond oil showed better performance under extreme pressure conditions and a greater weld point than mineral oils. Finally, an FT-IR spectroscopic analysis allowed determining that under the conditions of the current assays almond oil does not oxidize.